Biomaterials science : processing, properties, and applications - Narayan, Roger; Bandyopadhyay, Amit.; Bose, Susmita; American Ceramic Society; Materials Science & Technology Conference (2010 : Houston, Tex.) (Hoboken, N.J. : Wiley ; [Westerville, Ohio] : American Ceramic Society, 2011)
This book contains 18 papers from the Next Generation Biomaterials and Surface Properties of Biomaterials symposia held during the 2010 Materials Science and Technology (MS & T'10) meeting, October 17-21, 2010, Houston, Texas. Topics include: Biocompatible Coatings; Drug Delivery and Anti-Microbial Coatings; Ceramic and Metallic Biomaterials; Biomaterials for Tissue Engineering; and Surface Modification.
Front Matter -- Next Generation Biomaterials. Ultrafine-Grained Commercially Pure Titanium and Microstructure Response to Hydroxyapatite Coating Methods / Kayla Calvert, Kevin Trumble, Srinivasan Chandrasekar, Mark Hoffman -- Preparation of Porous Hydroxyapatite Scaffolds using Yeast as a Pore Forming Agent / Sophie C Cox, Kajal K Mallick -- Understanding the Influence of SrO Doping on the Mechanical Properties of [beta]- TCP Ceramics / Ken DeVoe, Amit Bandyopadhyay, Susmita Bose -- Dental Application Field Based on Nanostructural Chemically Bonded Ca-Aluminate / Leif Hermansson -- Freeze Extrusion Fabrication of 13-93 Bioactive Glass Scaffolds for Repair and Regeneration of Load-Bearing Bones / TS Huang, MN Rahaman, ND Doiphode, MC Leu, BS Bal, DE Day, X Liu -- Porous Biodegradable Scaffolds for Hard Tissue Engineering / Kajal K Mallick, James Winnett -- Synthesis of Nano Hydroxyapatite by Chemical Precipitation Using Different Surfactant Templates / Shahid Amin, Mohammad Mujahid -- Effect of TiB or YO Additions on Mechanical Biofunctionality of Ti-29Nb-13Ta-4.6Zr for Biomedical Applications / Mitsuo Niinomi, Masaaki Nakai, Satoshi Yonezawa, Xiu Song, Lei Wang -- Apatite Nano-Rods Array Grown on Glass Substrates in Aqueous Systems / A Osaka, Y Shirosaki, S Hayakawa, K Tsuru, E Fujii, K Kawabata -- Dielectric Properties of Porous Calcium Titanate (CaTiO) / G A Rott, F Zhang, Y Haba, W Kruger, E Burkel -- Nanocomposites of Poly(L-Lactic Acid) and Maghemite for Drug Delivery of Caffeine / A Vargas, F G Souza -- Surface Properties of Biomaterials. Hard and Wear Resistant Surfaces for Load Bearing Metal Implants / Vamsi Krishna Balla, Susmita Bose, Amit Bandyopadhyay -- Influence of Electro-Thermal Polarization on Surface Properties of Hydroxyapatite / S Bodhak, S Bose, A Bandyopadhyay -- Calcium Phosphate Ceramics in Drug Delivery and Bone Tissue Engineering / Susmita Bose, Solaiman Tarafder, Shashwat Banerjee, Amit Bandyopadhyay -- Nanoscale Hydroxyapatite Coatings on Ti: Simultaneous Enhancement of Mechanical and Biological Properties / Mangal Roy, Amit Bandyopadhyay, Susmita Bose -- Thermal Sprayed Bioceramics Coatings for Metallic Implants / TPS Sarao, H Singh, H Singh, R Chhibbe -- Role of Reinforced Materials in Thermal Sprayed Hydroxyapatite Coating on Bio Implants: A Review / Gurbhinder Singh, Surendra Singh, Satya Prakash -- Selective Laser Sintering Fabrication of 13-93 Bioactive Glass Bone Scaffolds / M Velez, K C R Kolan, M C Leu, G E Hilmas, R F Brown -- Author Index.
"This volume is a collection of eighteen research papers from the symposia on Next Generation Biomaterials and Surface Properties of Biomaterials, held during the 2010 Materials Science & Technology Conference & Exhibition (MS & T'10), Houston, TX, October 17-22, 2010"--Preface.
Includes bibliographical references and author index.
Print version record.
Keywords: Biomedical materials -- Congresses; Biomedical materials -- Surfaces -- Congresses; Biomedical materials; Biomedical materials -- Congresses; Biomedical materials -- Surfaces; Biomedical materials -- Surfaces -- Congresses; MEDICAL -- Allied Health Services -- Medical Technology; MEDICAL -- Biotechnology; MEDICAL -- Family & General Practice; MEDICAL -- Lasers in Medicine; TECHNOLOGY & ENGINEERING -- Biomedical; Biomedical materials; Biomedical materials -- Surfaces; Electronic books; Conference papers and proceedings